The transport service triad: a key unit of analysis. Issue 1 (8th January 2019) - Andersson, Dan; Dubois, Anna; Eriksson, Victor; Hulthén, Kajsa; Holma, Anne-Maria
Abstract : Purpose: The purpose of the paper is to identify and discuss the transport service triad (TST) as a key unit of analysis to understand the operations and conditions for change in freight transport systems at the micro level, i.e. at the level of analysis where business decisions and change interaction take place. Design/methodology/approach: The theoretical framing is rooted in the IMP approach and in the literature on triads. A case study approach is used to illustrate the TST by analyzing a case involving a wholesaler of installation products, tools and supplies, a main construction company and a transport service provider. Findings: The paper shows how the connections between the business relationships in the TST, influenced by connections to relationships outside the triad, impact on the efficiency in freight transport. The paper illustrates how analysis of TSTs can be applied in micro-level studies of change in freight transport systems and in supply networks. Research limitations/implications: The triadic approach is instrumental to understand change in the transport system because it includes all relevant parties and relationships of concern, as well as the logic framing of their actions. However, while arguing that TSTs are generic to their nature, each TST is unique and needs to be identified and analyzed in its specific context. Practical implications: The suggested framework may contribute to an understanding of the embeddedness of transport services in supply/business networks. The framework may support the development of new ways of operating and creating value for customers and offering sustainable transport solutions. Originality/value: From the transport policy makers' perspective, micro-level analysis is important to understand behavioral adjustments to new policies.